Case report: Paroxysmal nocturnal hemoglobinuria presenting with hemorrhagic esophageal varices - Du, Runsen; Zheng, Lihua; Liu, Peng; Zhao, Yaheng; Yang, Yan; Zhang, Lei; Zhao, Zengren (Frontiers in Medicine, 2023)
We report the case of a female who was cured of hemorrhagic esophageal varices caused by paroxysmal nocturnal hemoglobinuria (PNH) through transjugular intrahepatic portosystemic shunt (TIPS) treatment. PNH complicated by portal vein and visceral veins thrombosis without hepatic veins is extremely rare, and as such, it is easy to incorrectly treat due to lack of awareness. Hemorrhagic esophageal varices due to PNH with PVT have been reported in one case in 1974, and here, we report the second.